Curing behavior of thermosets for the use in a combined selective laser sintering process of polymers - Wudy, Katrin; Drummer, Dietmar (Solid Freeform Fabrication 2018: Proceedings of the 29th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2018, 2020)
Selective laser sintering (SLS) of polymers is an additive manufacturing process, which enables the production of functional technical components. Unfortunately, the SLS process is restricted regarding the materials that can be processed and thus resulting component properties are limited. The investigations in this study illustrates a totally new additive manufacturing process which combines reactive liquids like thermoset resins and thermoplastics to generates multi material SLS parts. To introduce thermoset resins into the regular SLS process, the time-temperature-dependent curing behavior of the thermoset and the infiltration behavior has to be understood in order to assess the process behavior. The curing behavior was analyzed by rotational viscosimeter. Furthermore, the fundamental infiltration behavior was analyzed with micro dosing infiltration experiments. Finally, a thermoset resin in combination with a dosing system was choosen for integration in a laser sintering system.
CRIS-Team Scopus Importer:2020-05-29